Perkembangan Penelitian Mikoriza di Papua** - Verena Agustini; Suharno Suharno; Supeni Sufaati (Jurusan Biologi FMIPA Universitas Cenderawasih, 2010)
The mycorrhizas are ‘balanced’ mutualistic associations in which the fungus and plant exchange commodities required for their growth and survival. The are many type of mycorrhizal namely endomycorrhiza, ectomycorrhiza, Orchid-mycorrhiza, ericoid mycorrhiza, and ectendo mycorrhiza. Most research is in endo and ectomycorrhiza, due to their role in Papua. Research in mycorrhiza has also been done recently. The research started in 2005 with ectomycorrhiza studies conducted by Suharno & Sufaati. Study on endomycorrhiza were begin in 2006 and orchid mycorrhiza in 2007. Exploration study of endomycorrhiza in corn plant at Koya Barat showed that there were 7 species of VAM namely Glomus sp1., Glomus sp2., Glomus sp3., Gigaspora sp., Acaulospora., Scutellospora sp1., and Scutellospora sp2. Similar research have also been done on other agriculture comodity, and the weed as well. Study on the endomycorrhiza associated with matoa (Pometia pinnata) found 13 species. Furtheremore, preliminary research on ectomycorrhiza showed that at least four species have been found at Mount Cycloops Nature Reserve, Jayapura. In Papua, there were 18 strain isolate of Scleroderma have been collected and 4 species were already identified. For orchid-mycorrhiza there were only 17 species has been found so far. Among them there species were identified: Rhizoctonia sp., Tulasnella sp., dan Ceratorhiza sp. The potency of mycorrhiza in Papua is high and need to be explored. Some isolate were already tested to variety of the growth of plant. The result showed that the isolate affected significantly. More exploration, compatibility test, and the role of mycorrhiza will be continued to study. The goals of all the study here was to find a good quality of isolate that can be used as a propagule to produce biofertilizer.Key words: endomycorrhiza, ectomycorrhiza, orchid-mycorrhiza, biofertilizer, Papua.